Liberalisme dan Tantangan Pendidikan Islam di Era Globalisasi: Analisis Perspektif Pendidikan Islam - Haniffah Dwi Ayunda; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
Globalization has significantly influenced various aspects of human life, including educational practices and perspectives on religious values. One of the prominent developments within this context is the spread of liberalism, a worldview that emphasizes individual freedom and rational thinking. Its growing influence has created both opportunities and challenges for Islamic education. On the one hand, liberal ideas encourage critical thinking and openness to scientific advancement. On the other hand, they may contribute to perspectives and practices that are not always in harmony with the fundamental teachings of Islam. This study examines the influence of liberalism on Islamic education in the era of globalization and explores the challenges as well as the responses developed by Islamic educational institutions. The research employs a qualitative descriptive approach through library research, drawing on scholarly articles indexed in SINTA and Scopus published within the last five years. The findings indicate that liberalism affects students' perspectives through the expansion of unrestricted freedom of thought, moral relativism, secular tendencies in education, and the growing influence of global digital culture. These developments have implications for the weakening of religious values, the emergence of moral challenges, and a shift toward more pragmatic educational orientations. In response, Islamic education needs to strengthen faith-based and character education, integrate scientific knowledge with the values of tawhid, and promote Islamic digital literacy. The study highlights the importance of maintaining the core principles of Islamic education while adapting to the demands and realities of a rapidly changing global environment.